Cataract Surgical Coverage and Visual Outcome using RAAB in Birnin Gwari Local Government Area, North West Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Cataract is the leading cause of blindness worldwide. It is responsible for 51% of blindness and accounting for 65.2 million blind people worldwide. Cataract surgery has been shown to be one of the most cost effective health care interventions.Aims:To determine the cataract surgical coverage (CSC) and visual outcome using RAAB in Birnin Gwari Local Government Area, North West Nigeria.Setting and Design:Population based cross sectional study.Materials and Methods:Rapid method of assessing avoidable blindness was used (RAAB) in the study. A total of 2162 out of 2530 registered eligible subjects were examined. Two stage cluster random sampling was used to select 59 clusters in 40 villages, and in each cluster, 50 subjects aged 40 years and above were selected using probability proportional to the size. Biodata of all eligible subjects were registered followed by visual acuity (VA) testing. Subjects with VA of